Effects of fatigue on temporal variables and their variability during a repetitive karate exercise - Aragones, D.; Eekhoff, A.; Horst, F.; Schöllhorn, W. I. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Despite the differential training approach has been successfully applied to improve skills by introducing variability, repetitive training pproaches are still common in most sports (e.g., karate). Increased variability has been reported with fatigue accumulation during repetitive endurance training (Cignetti et al., 2009). Thus, skill acquisition by repeating could be attributed to fatigue-induced variability. Accordingly, our aim was to analyze temporal variables and their variability in karate during a fatiguing exercise based on repetitions. METHODS: Sixteen healthy adults (5 women, 11 men) practicing karate with black and brown belts performed 9 sets of 60 mae-geri kicks (i.e., frontal kick) at submaximal intensity (alternating subsets of ten repetitions with right and left leg) with 90-seconds of rest period between sets. All kicks were performed at a frequency of 1 kick/2 seconds without impacting a target. Kinematic data were captured by 10 Oqus 310 infrared cameras (Qualisys AB, Sweden, 333 Hz) employing passive markers. Total kick time duration was divided into 2 phases (phase 1 from the start of the kicking foot movement until maximum knee flexion; phase 2 from this moment until full knee extension). Means and standard deviations (as a measure of variability) of the kick durations, peak angular velocities occurrence (of the hip, knee, ankle), and peak linear velocities of the kicking area of the foot (metatarsal heads) were compared within (between subsets of 10 repetitions) and between sets by means of Friedman ANOVA. RESULTS: Kicks had a statistically significant increase with fatigue accumulation within sets in total duration and phase 1 duration (mainly between the first subset of 10 repetitions and the rest); furthermore, peak velocities occurred later (mainly of the feet). Regarding variability, significant differences were found for duration (phase 1 and 2) within the last set, and for peak velocities occurrence of the foot and joints between different sets. DISCUSSION: With fatigue accumulation kick duration increases (phase 1 is much more affected than phase 2) and peak velocities of the feet occur later within sets. Moreover, the effects of fatigue are clearly manifested after the first subset of 10 repetitions, considering that subset 2 and 3 are not significantly different. Nevertheless, a 90-seconds rest period seems to be enough in order to produce previous values. Results demand further differentiated research related to absolute and relative variability and more variables should be considered to fully understand the effect of fatigue accumulation on variability during repetitive training.